Keabsahan Perkawinan Sesama Jenis Sebagai Gejala Sosial Dalam Perspektif Hukum Alam - Ismail Marzuki; Rhama Wisnu Wardhana (Jurnal Suara Hukum, 2022)
The issue of marriage is always interesting to study, this is because what is regulated in marriage is the relationship between men and women as husband and wife. Furthermore, marriage also regulates the obligations of the husband and wife towards the children born of their relationship. In its development, marriages that occur in society are not only carried out between men and women, but have reached marriages of the same gender or gender, both marriages between men and other men as husband and wife, as well as women with another woman. The purpose of this study is to determine the validity of same-sex marriage in the perspective of the flow of natural law. The method used is the juridical-normative method with a statutory approach and legal philosophy. The results of this study are that the flow of natural law is closely related to divine morality. Good and bad, wrong and right, proper and inappropriate, are measured according to divine moral standards. Therefore, human behavior and/or regulations made by humans that deviate and conflict with natural laws cannot be accepted and/or cannot be referred to as laws. Thus, marriage of the same gender in the context of national and state life in Indonesia is unacceptable and invalid because it is not in harmony with divine moral values.